Representation of an Asian-Australian Gay in Hsu-Ming Teo’s Behind the Moon - Amelberga Vita N.P. Astuti (Jurnal ILMU KOMUNIKASI, 2018)
This paper examines how a novel Behind the Moon (2005) provides literary representations of an Asian migrant’s transforming sexual identities in Australia. Applying Morris’s concept of a “politics of surveillance,” it argues that approaches of strict control leads to an initial clash of cultures, and ultimately either to mutual transformation or a reinforcement of lack of agency/sexual difference. The analysis shows that the novel displays aspects of the cultural complexities of sexual identity formation regarding the character’s identity as an Asian homosexual in Australia. As to transformation setting, the city is a spatial metaphor for cultural confinement and surveillance.